1996
DOI: 10.1017/s0954579400007367
|View full text |Cite
|
Sign up to set email alerts
|

Early risk factors and pathways in the development of early disruptive behavior problems

Abstract: This study examined risk factors from infancy associated with the development of preschool disruptive behavior problems across child, parent, and sociodemographic domains. Risk factors that consistently were associated with the prediction of disruptive behavior at age 5 years included disorganized attachment classification at 12 months, and maternal personality risk and child-rearing disagreements during the second year. In addition, infants with disorganized attachment status at 12 months whose mothers percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
155
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(178 citation statements)
references
References 55 publications
16
155
1
6
Order By: Relevance
“…In the PMCP, the Aggression subscale demonstrated adequate internal reliability (α=0.63). In a sample that was demographically similar to the PMCP, the Aggression subscale demonstrated a test-retest reliability of 0.59 over a period of 7-12 months (Shaw et al 1996).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the PMCP, the Aggression subscale demonstrated adequate internal reliability (α=0.63). In a sample that was demographically similar to the PMCP, the Aggression subscale demonstrated a test-retest reliability of 0.59 over a period of 7-12 months (Shaw et al 1996).…”
Section: Methodsmentioning
confidence: 95%
“…In the PMCP, the Aggression subscale demonstrated adequate internal reliability (α=0.63). In a sample that was demographically similar to the PMCP, the Aggression subscale demonstrated a test-retest reliability of 0.59 over a period of 7-12 months (Shaw et al 1996).Maternal Empathy-To assess maternal empathy, the Adolescent Parenting Inventory (API; Bavolek et al 1977) was administered to mothers when children were 24 months of age. The API was originally designed to identify maternal characteristics and beliefs associated with child maltreatment.…”
mentioning
confidence: 99%
“…Externalizing problems such as aggression, oppositional behavior, and attention problems are clear obstacles to the successful negotiation of these demands. Several studies have reported that early difficult temperament, parental psychopathology, and dysfunctional parenting predict externalizing problems at (pre)school age (e.g., Shaw et al 1996;Smith et al 2004). However, far fewer studies have examined whether such variables also predict changes in externalizing problems from toddlerhood into (pre)school age.…”
Section: Introductionmentioning
confidence: 99%
“…Modern attachment theorists have explored the importance of the parent-child attachment relationship in the way the mind processes interpersonal information to use as a psychosocial template for future relationships (Howe, 2005). Researchers have linked difficult early attachment relationships to children showing aggressive and disruptive behaviour, and adolescents who have anxiety disorders and/or impaired operational skills and self-regulation (Sroufe, 1983;Speltz et al, 1990;Lyons-Ruth et al, 1993;Jacobsen et al, 1994;Shaw et al, 1996;Warren et al, 1997). Neglected children show social and emotional difficulties as well as differences in brain size and structure (Hildyard and Wolfe, 2002;Perry, 2002).…”
Section: Practice Applicationmentioning
confidence: 99%